The Phenicien Carthaginian Purple Industry and Contemporary Design: An Intersection between Cultural Heritage, Sustainability and Creativity - Kallel, Houda Kohli; Falhi, Soumaya Gharsallah (Proceedings of the 2025 International Conference on Global Cultural and Creative Industries (ICGCCI 2025), 2025)
Fashion and cultural heritage play an essential role in preserving traditional skills and indigenous knowledge. In a context of globalisation, these aspects become vectors of transcultural creativity, particularly in interdisciplinary design projects. This summary examines how industry and the purple colour of the Carthaginians influence contemporary designers in various creative fields, while exploring the impact of sustainability and art on these practices. The methodological approach of this study is based on a qualitative analysis of the creative and craft practices of the Carthaginians, in particular their purple colour industry. An exploration of historical and cultural references was used to identify elements of traditional knowhow. Next, an analysis of the work of designers in the fields of fashion, graphic design and product design will be interpreted to understand how the crimson industry influences their creations. The results show that the Carthaginian purple industry, a symbol of power and prestige, is a major inspiration for contemporary designers. This rare pigment, extracted from molluscs, was once used to dye the clothes of the elite. Today, it is being reinterpreted in design projects, underlining the importance of sustainability and respect for natural resources. The designers interviewed highlighted the influence of the colour's cultural symbolism, as well as its aesthetic appeal in sectors such as fashion, interior design and graphics.This research reveals that the intersection of art, sustainability and design can act as a catalyst to revive craft traditions, while offering endless creative possibilities. Designers are drawing on Carthaginian heritage to develop innovative creations, adoping practices that are more respectful of the environment. In this way, traditional craftsmanship becomes a source of inspiration for contemporary creation, linking past and present.
Series Title: Advances in Social Science, Education and Humanities Research
Keywords: Artisanat – Djerba; Murex – Djerba

Un Tunisien ressuscite la pourpre, ce prestigieux pigment antique (Metro, 2020)
Sa passion pour l’histoire antique, Mohamed Ghassen Nouira la vit dans sa cuisine: c’est là que ce Tunisien redécouvre peu à peu, après des années de tâtonnements, les secrets ...
Keywords: Murex – Djerba

En Tunisie, un passionné de la pourpre ressuscite ce pigment antique - Larbi, Kaouther (AFP, 2020)
Sa passion pour l'histoire antique, Mohamed Ghassen Nouira la vit dans sa cuisine: c'est là que ce Tunisien redécouvre peu à peu, après des années de tâtonnements, les secrets ...
Keywords: Murex – Djerba

Passion for purple revives ancient dye in Tunisia - Larbi, Kaouther (AFP, 2020)
A Tunisian man has pieced together bits of a local secret linked to ancient emperors: how to make a prized purple dye using the guts of a sea snail. "At the ...
Keywords: Murex – Djerba

Un passionné de la pourpre ressuscite ce pigment antique (All Africa (web site ref.) - allAfrica, 2020)
Sa passion pour l'histoire antique, Mohamed Ghassen Nouira la vit dans sa cuisine: c'est là que ce Tunisien redécouvre peu à peu, après des années de tâtonnements, les secrets ...
Keywords: Murex – Djerba